Studies of impurities behaviour for the optimization of plasmas and heating scenarios at tokamaks in perspective for ITER - Czarnecka, A. (Вопросы атомной науки и техники, 2018)
This contribution reports on the recent progress of integration methods to control and minimise W and mid-Z
impurity content for the optimization of plasmas and heating scenarios at tokamaks. The operational setup of
diagnostics for impurity control is briefly described. It was found out that different parameters such as auxiliary
heating power, deuterium gas injection rate, impurity seeding, density profile, and ELM’s frequency affect the
behavior of impurities. Furthermore, ICRH use is reviewed and methods for optimisation simultaneously RF
coupling and impurity control are presented. Мова йде про теперішній прогрес у розвитку методів контролю і мінімізації вольфраму та інших домішок
із середнім Z для оптимізації плазми та сценаріїв нагріву плазми в токамаках. Коротко описано комплекс
діагностики для контролю домішок. Виявлено, що різні параметри, такі як додаткова потужність нагріву,
швидкість вприскування дейтерію, джерело домішок, профіль густини та частота ELMів, впливають на
поведінку домішок. Крім того, розглядається також використання ICRH та методів одночасної оптимізації
RF зв’язку і контролю домішок. Речь идет о недавнем прогрессе в развитии методов контроля и минимизации вольфрама и других
примесей со средним Z для оптимизации плазмы и сценариев нагрева плазмы в токамаках. Коротко описан
комплекс диагностики для контроля примесей. Обнаружено, что различные параметры, такие как
дополнительная мощность нагрева, скорость впрыскивания дейтерия, источник примесей, профиль
плотности и частота ELMов, влияют на поведение примесей. Кроме того, рассматривается использование
ICRH и методов одновременной оптимизации RF связи и контроля примесей.